2016
DOI: 10.3390/e18120432
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Based Person Authentication Using a Fuzzy Entropy-Related Approach with Two Electrodes

Abstract: Person authentication, based on electroencephalography (EEG) signals, is one of the directions possible in the study of EEG signals. In this paper, a method for the selection of EEG electrodes and features in a discriminative manner is proposed. Given that EEG signals are unstable and non-linear, a non-linear analysis method, i.e., fuzzy entropy, is more appropriate. In this paper, unlike other methods using different signal sources and patterns, such as rest state and motor imagery, a novel paradigm using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…Mu, Hu and Min enhanced the performance of EEG biometric using feature extraction based on fuzzy entropy, and feature selection based on Fisher distance. In their experiment, data was captured from 10 subjects using two electrodes, namely, FP1 and FP2.…”
Section: Emerging Biometric Technologiesmentioning
confidence: 99%
“…Mu, Hu and Min enhanced the performance of EEG biometric using feature extraction based on fuzzy entropy, and feature selection based on Fisher distance. In their experiment, data was captured from 10 subjects using two electrodes, namely, FP1 and FP2.…”
Section: Emerging Biometric Technologiesmentioning
confidence: 99%
“…The final result was achieved by averaging the outcome produced in the corresponding test repeated 10 times (for different subjects and different feature sets). Using this evaluation scheme, the dependency of the training and test features was removed, thus avoiding the over-fitting problem [37][38][39][40][41][42]. In particular, though GB is a more capable and practical boosting algorithm, like most other classifiers, GB also had the problem of over-fitting when dealing with very noisy data.…”
Section: Classificationmentioning
confidence: 99%
“…Based on the literature [36][37][38][39], of the four feature sets, FE out-performed the other feature sets. DT was the best among several classifiers, while SVM was the weakest.…”
Section: Effect Of Noise: Dt Classifier Vs Knn Classifier Vs Svm CLmentioning
confidence: 99%
“…The authors have shown that using FEn as a feature results in classification accuracy greater than 87.3%, while only two frontal electrodes are required. The study was heavily based on the algorithm's robustness to noise and sensitivity to different levels of signal randomness which eventually aid in the reduction of electrodes and the improvement of classification rates simultaneously [23].…”
Section: Introductionmentioning
confidence: 99%